Anti-pollution protective adhesive tape capable of self-stripping at high temperature
By adding modified nanotitanium dioxide composite and perfluoropolyether siloxane to the adhesive of the anti-pollution protection tape, the problem of poor adhesive performance and anti-fouling performance at high temperature is solved, and the anti-pollution protection effect of self-peeling at high temperature without leaving any residual glue is achieved.
Patent Information
- Application Number
- CN202510176665.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-05-09
AI Technical Summary
The existing anti-fouling tape has poor adhesive performance and anti-fouling properties at high temperatures, and it is easy to leave residual glue after peeling, resulting in surface contamination and damage.
Modified nanotitanium dioxide composite is used as an anti-pollution additive, combined with perfluoropolyether siloxane, to enhance the anti-fouling performance and stability of the adhesive, forming a self-peeled anti-pollution protection tape at high temperature.
Maintain good adhesive performance and anti-fouling properties at high temperatures, and no residual glue will be left after peeling, which improves the service life and cleanliness of the tape.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, and in particular to an anti-pollution protective adhesive tape capable of self-peeling at high temperature. Background Art
[0002] Antifouling tape is used to prevent the wall surfaces on both sides of the seam from being stained by the color of the sealing material during the sealing construction, so as to keep the wall surface clean and tidy, and make the sealed seam have an overall "horizontal and vertical" viewing effect. The antifouling adhesive phase can be pasted on the surface of the sealing material in the seam to prevent the sealing material from being stained or damaged when the wall surface is decoratively sprayed. Commonly used antifouling tapes include glass tape, pressure-sensitive tape, kraft paper, etc. In the construction, automobile manufacturing, aerospace and other industries, the demand for material protection in high-temperature working environments is increasing. Traditional protective materials often cannot maintain stable adhesion properties at high temperatures, and are prone to residual glue during the peeling process, resulting in surface contamination and damage. Therefore, the development of a protective material that can effectively protect sensitive surfaces in high-temperature environments and can be easily peeled off without leaving residual glue after the operation is completed has become an important research direction in the field of chemical materials science.
[0003] Self-peeling anti-pollution protective tape at high temperature This tape must have stability and reliability under high temperature conditions, as well as the ability to automatically peel off without leaving any residue after the protection task is completed. This not only involves the chemical formula design of the adhesive, but also needs to consider the physical properties of the material and the surface treatment technology. With the improvement of environmental awareness and the refinement of industrial production, the demand for environmentally friendly protective materials that can provide effective protection under extreme conditions is increasing. Therefore, the research and development of anti-pollution protective tapes with self-peeling properties can not only meet the strict requirements for material protection in industrial production, but also reduce environmental pollution and improve production efficiency. It has important practical application value and broad market prospects.
[0004] However, the anti-fouling coatings that are currently being studied more in the market are hydrophobic, hydrophilic or photocatalytic self-cleaning coatings, among which the most studied are super-hydrophilic titanium dioxide films that have the function of photocatalytically degrading organic matter. However, there are few studies that have both self-peeling anti-fouling and self-cleaning effects.
[0005] Chinese invention patent 202411156704.8 discloses a peelable pressure-sensitive adhesive tape without residual adhesive and its preparation method. It includes the following steps: applying a release agent on one surface of a substrate and drying; then directly applying the pressure-sensitive adhesive obtained by stirring polyacrylic acid resin and curing agent on the other surface of the substrate, drying and rolling, and obtaining a peelable pressure-sensitive adhesive tape without residual adhesive; the polyacrylic acid resin includes the following raw materials by weight: 80-90 parts of soft monomer, 10-20 parts of hard monomer, 2-8 parts of functional monomer, 1-3 parts of auxiliary agent, 1-4 parts of initiator, and 300-400 parts of solvent; although the tape prepared by the invention has good viscosity and stability, the adhesive performance and anti-fouling performance of the tape at high temperature are poor, and it is necessary to improve the comprehensive performance during high temperature operation. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides an anti-pollution protective tape that can be self-peeled at high temperature.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer, wherein the anti-pollution protective layer is obtained by uniformly coating an adhesive film made of an adhesive on the surface of the substrate; the raw material of the adhesive comprises an anti-pollution additive; the anti-pollution additive is a modified nano titanium dioxide composite.
[0008] The substrate is any one of PE, PP and thermoplastic polyurethane.
[0009] The release agent is a silicone release agent.
[0010] The adhesive is composed of the following raw materials in parts by weight: 40-70 parts by weight of soft monomer, 5-12 parts by weight of hard monomer, 3-6 parts by weight of functional monomer, 0.5-2 parts by weight of crosslinking agent, 4-7 parts by weight of anti-pollution additive, 0.5-2 parts by weight of di-tert-butyl peroxide, and 150-300 parts by weight of solvent.
[0011] The soft monomer is at least one of ethyl acrylate, butyl acrylate, isooctyl acrylate and lauryl methacrylate.
[0012] The hard monomer is at least one of methyl acrylate, isopropyl methacrylate, styrene, acrylonitrile, methyl methacrylate and acrylamide.
[0013] The functional monomer is one or more of methacrylic acid, 2-hydroxyethyl acrylate, diphenyl (4-vinylphenyl) phosphine oxide, glycidyl acrylate, and N,N-dimethylacrylamide.
[0014] The crosslinking agent is at least one of hydroxyethyl acrylate, bis(1-vinyl imidazole-2-)ketone, and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane.
[0015] Titanium dioxide has excellent photocatalytic activity. When titanium dioxide is exposed to ultraviolet rays, a photocatalytic reaction will occur to generate oxidative free radicals and superoxide ions; these free radicals and ions will further react with water and oxygen to generate highly oxidizing hydroxyl groups and hydrogen peroxide; hydroxyl groups and hydrogen peroxide can decompose organic and inorganic substances attached to their surfaces, thereby achieving the purpose of "self-cleaning" and anti-fouling. However, as a powdered inorganic material, nano titanium dioxide is difficult to adhere firmly to the substrate, so it needs to be modified to form an organic-inorganic composite material, which can improve the adhesion and durability of titanium dioxide on the tape substrate. Organic matter can also provide solubility, making it easier to apply during coating.
[0016] The present invention adds an anti-pollution additive to the adhesive of the anti-pollution protective layer, so that the adhesive has excellent anti-pollution performance, can effectively prevent stains from adhering to the surface and is easy to clean; at the same time, the durability and stability of the adhesive are enhanced, and the service life of the adhesive tape is extended.
[0017] The preparation method of the modified nano titanium dioxide composite is as follows: S1. Mix 3-aminopropyl pentamethyldisiloxane, succinic anhydride and N,N-dimethylformamide and stir evenly, add nano-titanium dioxide and perform ultrasound, and then heat and stir to obtain carboxylated titanium dioxide; S2, take methyl 2,6-diisocyanatohexanoate and toluene and stir evenly, then add terminal hydroxyl perfluoropolyether and N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, heat and stir, then add γ-glycidyloxypropyltrimethoxysilane, continue to react, and obtain perfluoropolyether siloxane; S3, ultrasonically dispersing the carboxylated titanium dioxide and toluene, adding the perfluoropolyether siloxane, continuing ultrasonication, and finally reacting at 90-100° C. for 4-8 hours to obtain a modified nano-titanium dioxide composite.
[0018] The surface of nano-titanium dioxide particles has been modified to have a large number of -COOH groups, which are super hydrophilic and easy to agglomerate, forming irregular aggregates and agglomerates. The hydrophobicity and oleophobicity of perfluoropolyether siloxane are better than those of ordinary siloxane, and it also has better gloss and transparency. This property helps to improve the anti-fouling property of the crystal coating, which is an important anti-fouling performance indicator for anti-fouling tape products.
[0019] The perfluoropolyether siloxane prepared by the present invention not only contains a large number of -OH groups and -NH2 groups, which can react with the surface groups of titanium dioxide particles on the surface of titanium dioxide particles to undergo a dehydration reaction, but also contains hydrophobic -F and -CH3 groups, so that the perfluoropolyether siloxane titanium dioxide nanoparticles have lower surface energy and can effectively improve the hydrophobicity of the adhesive. The perfluoropolyether siloxane has excellent waterproof, oil-proof and antifouling properties and can be used to modify titanium dioxide to prepare various antifouling agents. At the same time, titanium dioxide also has a porous structure and can effectively absorb impurities. The two work synergistically to jointly improve the antifouling performance of the adhesive and the viscosity of the tape.
[0020] Specific reaction mechanism: S1 uses 3-aminopropyl pentamethyldisiloxane and succinic anhydride as reaction raw materials and N,N-dimethylformamide as solvent. Succinic anhydride reacts with the amino group of 3-aminopropyl pentamethyldisiloxane to form a carboxylic acid amide bond to obtain a carboxylated silane compound; nano-titanium dioxide is added for ultrasonic dispersion to ensure that TiO2 is evenly dispersed in the solution, increase the contact area, and promote the reaction. The carboxylated silane compound reacts with the hydroxyl group on the surface of TiO2 to form carboxylated titanium dioxide; S2 uses 2,6-diisocyanatohexanoic acid methyl ester and terminal hydroxyl perfluoropolyether as reaction raw materials. The NCO group of 2,6-diisocyanatohexanoic acid methyl ester reacts with the terminal hydroxyl perfluoropolyether. The hydroxyl groups of the polyether react to form a carbamate bond, and N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane is added to the above solution, and heated to form a siloxane group, and then γ-glycidyloxypropyltrimethoxysilane is added to the reaction system to further increase the content of the siloxane group and improve the crosslinking degree of the reaction product to obtain perfluoropolyether siloxane; S3 uses carboxylated titanium dioxide and perfluoropolyether siloxane as reaction raw materials, and under heating conditions, the perfluoropolyether siloxane further reacts with the carboxyl group on the surface of the carboxylated titanium dioxide to form a stable siloxane group, thereby enhancing the surface modification of TiO2 and obtaining a modified nano-titanium dioxide composite.
[0021] The invention adds a modified nano titanium dioxide compound to the adhesive, which can not only enhance the adhesive force of the tape, but also enhance the antifouling performance of the tape. Due to its surface modification, the modified nano titanium dioxide compound can provide more active sites, enhance the interaction with the tape substrate, thereby improving the adhesive force, and the modified nano titanium dioxide compound can improve the stability of the tape in a high temperature environment, and keep the adhesive performance from decreasing; due to the high surface energy and photocatalytic activity of the modified nano titanium dioxide compound, the super hydrophobic performance of perfluoropolyether siloxane can effectively reduce the surface energy of the tape and the interface, thereby improving the hydrophobic performance of the adhesive, and finally reduce the adsorption of pollutants on the surface of the tape, and keep the tape clean.
[0022] Preferably, the preparation method of the modified nano titanium dioxide composite is as follows: S1, 2-5 parts by weight of 3-aminopropyl pentamethyldisiloxane, 1-3 parts by weight of succinic anhydride and 30-80 parts by weight of N,N-dimethylformamide are mixed and stirred evenly, 7-14 parts by weight of nano titanium dioxide are added, and dispersed at an ultrasonic power of 100-300 W and an ultrasonic frequency of 20-70 kHz for 30-60 min, and then stirred at 30-45 ° C and 400-800 rpm for 2-5 h, filtered, washed, and dried to obtain carboxylated titanium dioxide; S2, take 1-4 parts by weight of methyl 2,6-diisocyanatohexanoate and 8-20 parts by weight of toluene and stir evenly, then add 8-16 parts by weight of terminal hydroxyl perfluoropolyether and 1-4 parts by weight of N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, stir at 35-45° C. and 400-800 rpm for 5-10 hours, then add 1-3 parts by weight of γ-glycidyloxypropyltrimethoxysilane, continue to react for 3-8 hours, and remove the solvent by distillation under reduced pressure to obtain perfluoropolyether siloxane; S3. Mix 5-12 parts by weight of the above carboxylated titanium dioxide with 50-120 parts by weight of toluene, and ultrasonically disperse them for 40-90 minutes at an ultrasonic power of 100-300 W and an ultrasonic frequency of 20-70 kHz, then add 1-3 parts by weight of the above perfluoropolyether siloxane, continue ultrasonication for 15-30 minutes, and finally place at 90-100° C. for reaction for 4-8 hours. After the reaction is completed, centrifuge, wash, and dry to obtain a modified nano titanium dioxide composite.
[0023] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying it; then directly coating a film made of an adhesive on the other surface of the substrate, drying it, and rolling it up to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0024] Beneficial effects of the present invention: The present invention provides a high-temperature self-peeling anti-pollution protective tape and a preparation method thereof. The present invention adds an anti-pollution additive to the adhesive of the anti-pollution protective layer, so that the adhesive has excellent anti-pollution performance, can effectively prevent stains from adhering to the surface and is easy to clean; at the same time, the durability and stability of the adhesive are enhanced, and the service life of the tape is extended. In addition, the preparation method of the present invention is simple, the raw materials are easily available, and the obtained tape has high adhesion performance at high temperature and good anti-pollution performance. DETAILED DESCRIPTION
[0025] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0026] Introduction of some raw materials in this application: The PE substrate is from Kunshan Jinsheng Adhesive Products Co., Ltd., item number HH5070KS29OC.
[0027] N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, CAS: 1760-24-3.
[0028] The silicone release agent is provided by Shenzhen Kanglibang Technology Co., Ltd. with a viscosity of 1000~100,000 cPs.
[0029] The hydroxy-terminated perfluoropolyether was provided by Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., item number lnb-162.
[0030] Example 1 A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer. The anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate. The coating thickness is 25 μm. The substrate is PE.
[0031] The release agent is an organic silicon release agent, and the coating thickness is 20 μm.
[0032] The adhesive is composed of the following raw materials in parts by weight: 50 parts by weight of soft monomer, 8 parts by weight of hard monomer, 4 parts by weight of functional monomer, 1 part by weight of crosslinking agent, 5 parts by weight of anti-pollution additive, 1 part by weight of di-tert-butyl peroxide, and 200 parts by weight of solvent.
[0033] The soft monomer is ethyl acrylate.
[0034] The hard monomer is a mixture of methyl acrylate and acrylonitrile in a mass ratio of 4:1.
[0035] The functional monomer is 2-hydroxyethyl acrylate.
[0036] The crosslinking agent is bis(1-vinyl imidazole-2-)ketone.
[0037] The anti-pollution additive is a modified nano titanium dioxide composite; the preparation method of the modified nano titanium dioxide composite is as follows: S1, 3 parts by weight of 3-aminopropyl pentamethyldisiloxane, 2 parts by weight of succinic anhydride and 50 parts by weight of N,N-dimethylformamide were mixed and stirred evenly, 10 parts by weight of nano titanium dioxide were added, and the mixture was dispersed at an ultrasonic power of 200 W and an ultrasonic frequency of 40 kHz for 40 min, and then stirred at 40° C. and 600 rpm for 3 h, filtered, washed, and dried to obtain carboxylated titanium dioxide; S2, take 2 parts by weight of methyl 2,6-diisocyanatohexanoate and 10 parts by weight of toluene and stir evenly, then add 12 parts by weight of terminal hydroxyl perfluoropolyether and 2 parts by weight of N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, stir at 40°C and 600rpm for 8h, then add 2 parts by weight of γ-glycidyloxypropyltrimethoxysilane, continue to react for 5h, and remove the solvent by distillation under reduced pressure to obtain perfluoropolyether siloxane; S3. Mix 8 parts by weight of the above carboxylated titanium dioxide with 80 parts by weight of toluene, and ultrasonically disperse them for 50 minutes at an ultrasonic power of 200 W and an ultrasonic frequency of 40 kHz, then add 2 parts by weight of the above perfluoropolyether siloxane, continue ultrasonication for 20 minutes, and finally place at 95°C for reaction for 6 hours. After the reaction is completed, centrifuge, wash, and dry to obtain a modified nano titanium dioxide composite.
[0038] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying the release agent; then directly coating an adhesive film made of an adhesive on the other surface of the substrate, drying the adhesive film, and rolling the adhesive film to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0039] Example 2 A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer. The anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate. The coating thickness is 25 μm. The substrate is PE.
[0040] The release agent is an organic silicon release agent, and the coating thickness is 20 μm.
[0041] The adhesive is composed of the following raw materials in parts by weight: 40 parts by weight of soft monomer, 5 parts by weight of hard monomer, 3 parts by weight of functional monomer, 0.5 parts by weight of crosslinking agent, 4 parts by weight of anti-pollution additive, 0.5 parts by weight of di-tert-butyl peroxide, and 150 parts by weight of solvent.
[0042] The soft monomer is ethyl acrylate.
[0043] The hard monomer is a mixture of methyl acrylate and acrylonitrile in a mass ratio of 4:1.
[0044] The functional monomer is 2-hydroxyethyl acrylate.
[0045] The crosslinking agent is bis(1-vinyl imidazole-2-)ketone.
[0046] The anti-pollution additive is a modified nano titanium dioxide composite; the preparation method of the modified nano titanium dioxide composite is as follows: S1, 2 parts by weight of 3-aminopropyl pentamethyldisiloxane, 1 part by weight of succinic anhydride and 30 parts by weight of N,N-dimethylformamide were mixed and stirred evenly, 7 parts by weight of nano titanium dioxide were added and dispersed at an ultrasonic power of 100 W and an ultrasonic frequency of 20 kHz for 30 min, and then stirred at 30° C. and 400 rpm for 2 h, filtered, washed and dried to obtain carboxylated titanium dioxide; S2, take 1 part by weight of 2,6-diisocyanatohexanoic acid methyl ester and 8 parts by weight of toluene, stir evenly, then add 8 parts by weight of terminal hydroxyl perfluoropolyether and 1 part by weight of N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, stir at 35°C and 400rpm for 5h, then add 1 part by weight of γ-glycidyloxypropyltrimethoxysilane, continue to react for 3h, and remove the solvent by distillation under reduced pressure to obtain perfluoropolyether siloxane; S3. Mix 5 parts by weight of the above carboxylated titanium dioxide with 50 parts by weight of toluene, and ultrasonically disperse them for 40 minutes at an ultrasonic power of 100 W and an ultrasonic frequency of 20 kHz, then add 1 part by weight of the above perfluoropolyether siloxane, continue ultrasonication for 15 minutes, and finally place at 90°C for reaction for 4 hours. After the reaction is completed, centrifuge, wash, and dry to obtain a modified nano titanium dioxide composite.
[0047] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying the release agent; then directly coating an adhesive film made of an adhesive on the other surface of the substrate, drying the adhesive film, and rolling the adhesive film to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0048] Example 3 A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer. The anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate. The coating thickness is 25 μm. The substrate is PE.
[0049] The release agent is an organic silicon release agent, and the coating thickness is 20 μm.
[0050] The adhesive is composed of the following raw materials in parts by weight: 70 parts by weight of soft monomer, 12 parts by weight of hard monomer, 6 parts by weight of functional monomer, 2 parts by weight of crosslinking agent, 7 parts by weight of anti-pollution additive, 2 parts by weight of di-tert-butyl peroxide, and 300 parts by weight of solvent.
[0051] The soft monomer is ethyl acrylate.
[0052] The hard monomer is a mixture of methyl acrylate and acrylonitrile in a mass ratio of 4:1.
[0053] The functional monomer is 2-hydroxyethyl acrylate.
[0054] The crosslinking agent is bis(1-vinyl imidazole-2-)ketone.
[0055] The anti-pollution additive is a modified nano titanium dioxide composite; the preparation method of the modified nano titanium dioxide composite is as follows: S1, 5 parts by weight of 3-aminopropyl pentamethyldisiloxane, 3 parts by weight of succinic anhydride and 80 parts by weight of N,N-dimethylformamide were mixed and stirred evenly, 14 parts by weight of nano titanium dioxide were added, and the mixture was dispersed at an ultrasonic power of 300 W and an ultrasonic frequency of 70 kHz for 60 min, and then stirred at 45 ° C and 800 rpm for 5 h, filtered, washed, and dried to obtain carboxylated titanium dioxide; S2, take 4 parts by weight of methyl 2,6-diisocyanatohexanoate and 20 parts by weight of toluene and stir evenly, then add 16 parts by weight of terminal hydroxyl perfluoropolyether and 4 parts by weight of N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, stir at 45°C and 800rpm for 10h, then add 3 parts by weight of γ-glycidyloxypropyltrimethoxysilane, continue to react for 8h, and remove the solvent by distillation under reduced pressure to obtain perfluoropolyether siloxane; S3. Mix 12 parts by weight of the above carboxylated titanium dioxide with 120 parts by weight of toluene, and ultrasonically disperse them for 90 minutes at an ultrasonic power of 300 W and an ultrasonic frequency of 70 kHz, then add 3 parts by weight of the above perfluoropolyether siloxane, continue ultrasonication for 30 minutes, and finally place it at 100°C for reaction for 8 hours. After the reaction is completed, centrifuge, wash, and dry to obtain a modified nano titanium dioxide composite.
[0056] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying the release agent; then directly coating an adhesive film made of an adhesive on the other surface of the substrate, drying the adhesive film, and rolling the adhesive film to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0057] Comparative Example 1 A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer. The anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate. The coating thickness is 25 μm. The substrate is PE.
[0058] The release agent is an organic silicon release agent, and the coating thickness is 20 μm.
[0059] The adhesive is composed of the following raw materials in parts by weight: 50 parts by weight of soft monomer, 8 parts by weight of hard monomer, 4 parts by weight of functional monomer, 1 part by weight of crosslinking agent, 5 parts by weight of anti-pollution additive, 1 part by weight of di-tert-butyl peroxide, and 200 parts by weight of solvent.
[0060] The soft monomer is ethyl acrylate.
[0061] The hard monomer is a mixture of methyl acrylate and acrylonitrile in a mass ratio of 4:1.
[0062] The functional monomer is 2-hydroxyethyl acrylate.
[0063] The crosslinking agent is bis(1-vinyl imidazole-2-)ketone.
[0064] The anti-pollution additive is modified nano titanium dioxide; the preparation method of the modified nano titanium dioxide is as follows: 3 parts by weight of 3-aminopropyl pentamethyldisiloxane, 2 parts by weight of succinic anhydride and 50 parts by weight of N,N-dimethylformamide are mixed and stirred evenly, 10 parts by weight of nano titanium dioxide are added and dispersed at an ultrasonic power of 200 W and an ultrasonic frequency of 40 kHz for 40 minutes, and then stirred at 40° C. and 600 rpm for 3 hours, filtered, washed, and dried to obtain modified titanium dioxide.
[0065] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying the release agent; then directly coating an adhesive film made of an adhesive on the other surface of the substrate, drying the adhesive film, and rolling the adhesive film to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0066] Comparative Example 2 A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer. The anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate. The coating thickness is 25 μm. The substrate is PE.
[0067] The release agent is an organic silicon release agent, and the coating thickness is 20 μm.
[0068] The adhesive is composed of the following raw materials in parts by weight: 50 parts by weight of soft monomer, 8 parts by weight of hard monomer, 4 parts by weight of functional monomer, 1 part by weight of crosslinking agent, 5 parts by weight of anti-pollution additive, 1 part by weight of di-tert-butyl peroxide, and 200 parts by weight of solvent.
[0069] The soft monomer is ethyl acrylate.
[0070] The hard monomer is a mixture of methyl acrylate and acrylonitrile in a mass ratio of 4:1.
[0071] The functional monomer is 2-hydroxyethyl acrylate.
[0072] The crosslinking agent is bis(1-vinyl imidazole-2-)ketone.
[0073] The anti-pollution additive is a modified nano titanium dioxide composite; the preparation method of the modified nano titanium dioxide composite is as follows: S1: 2 parts by weight of methyl 2,6-diisocyanatohexanoate and 10 parts by weight of toluene were stirred evenly, and then 12 parts by weight of terminal hydroxyl perfluoropolyether and 2 parts by weight of N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane were added, and stirred at 40° C. and 600 rpm for 8 h, and then 2 parts by weight of γ-glycidyloxypropyltrimethoxysilane were added, and the reaction was continued for 5 h, and the solvent was removed by distillation under reduced pressure to obtain perfluoropolyether siloxane; S2. Mix 8 parts by weight of titanium dioxide with 80 parts by weight of toluene, and ultrasonically disperse them for 50 minutes at an ultrasonic power of 200 W and an ultrasonic frequency of 40 kHz, then add 2 parts by weight of the above-mentioned perfluoropolyether siloxane, continue ultrasonication for 20 minutes, and finally place it at 95°C for reaction for 6 hours. After the reaction is completed, centrifuge, wash, and dry to obtain a modified nano titanium dioxide composite.
[0074] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying the release agent; then directly coating an adhesive film made of an adhesive on the other surface of the substrate, drying the adhesive film, and rolling the adhesive film to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0075] Comparative Example 3 A high-temperature self-peeling anti-pollution protective tape comprises a substrate, a release agent and an anti-pollution protective layer. The anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate. The coating thickness is 25 μm. The substrate is PE.
[0076] The release agent is an organic silicon release agent, and the coating thickness is 20 μm.
[0077] The adhesive is composed of the following raw materials in parts by weight: 50 parts by weight of soft monomer, 8 parts by weight of hard monomer, 4 parts by weight of functional monomer, 1 part by weight of crosslinking agent, 5 parts by weight of anti-pollution additive, 1 part by weight of di-tert-butyl peroxide, and 200 parts by weight of solvent.
[0078] The soft monomer is ethyl acrylate.
[0079] The hard monomer is a mixture of methyl acrylate and acrylonitrile in a mass ratio of 4:1.
[0080] The functional monomer is 2-hydroxyethyl acrylate.
[0081] The crosslinking agent is bis(1-vinyl imidazole-2-)ketone.
[0082] The preparation method of the anti-pollution additive is as follows: 2 parts by weight of 2,6-diisocyanatohexanoic acid methyl ester and 10 parts by weight of toluene are mixed evenly, and then 12 parts by weight of terminal hydroxyl perfluoropolyether and 2 parts by weight of N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane are added, and the mixture is stirred at 40° C. and 600 rpm for 8 hours, and then 2 parts by weight of γ-glycidyloxypropyltrimethoxysilane are added, and the reaction is continued for 5 hours, and the solvent is removed by reduced pressure distillation to obtain perfluoropolyether siloxane.
[0083] The method for preparing the anti-pollution protective tape that can be peeled off at high temperature comprises the following steps: coating a release agent on one surface of a substrate and drying the release agent; then directly coating an adhesive film made of an adhesive on the other surface of the substrate, drying the adhesive film, and rolling the adhesive film to obtain the anti-pollution protective tape that can be peeled off at high temperature.
[0084] Test Example 1 Adhesion and peel strength test of the anti-pollution protective tape that self-peeled off at high temperature: The adhesion was measured by method A in the national standard GB / T4851-2014 "Test method for adhesion of adhesive tapes", and the prepared anti-pollution protective tape that self-peeled off at high temperature was aged at 110°C for 72h (heat aging), and the adhesion was tested again in the same way; the glass strength was measured by method 1 in the national standard GB / T2792-2014 "Test method for peel strength of adhesive tapes", 5 groups were tested in each group, and the average value was taken. The test results are shown in Table 1.
[0085] Table 1 Adhesion and peel strength test results of self-peeling anti-pollution protective tape at high temperature Test Example 2 Anti-pollution experiment: The anti-pollution protective tape that peels off at high temperature was attached to plain glass. After being treated at 60°C and 90% RH for 168 hours, the protective tape was removed and the surface condition of the plain glass was observed. The results are shown in Table 2.
[0086] Table 2 Anti-fouling performance test results of self-peeling anti-fouling protective tape at high temperature The high-temperature self-peeling anti-pollution protective tape prepared by the present invention has good adhesion at high temperatures and also has good anti-fouling performance. Comparing Example 1 and Comparative Example 1, it can be seen that the surface of the nano titanium dioxide particles has been modified to have a large number of -COOH groups, showing super hydrophilicity, and is easy to agglomerate to produce irregular aggregates and agglomerates. The hydrophobicity and oleophobicity of perfluoropolyether siloxane are better than those of ordinary siloxane, and it has better gloss and transparency. This property helps to improve the anti-fouling property of the crystal coating layer, which is an important anti-fouling performance indicator for anti-fouling tape products.
[0087] The perfluoropolyether siloxane prepared by the present invention not only contains a large number of -OH groups and -NH2 groups, which can react with the surface groups of titanium dioxide particles on the surface of titanium dioxide particles to undergo a dehydration reaction, but also contains hydrophobic -F and -CH3 groups, so that the perfluoropolyether siloxane titanium dioxide nanoparticles have lower surface energy and can effectively improve the hydrophobicity of the adhesive. The perfluoropolyether siloxane has excellent waterproof, oil-proof and antifouling properties and can be used to modify titanium dioxide to prepare various antifouling agents. At the same time, titanium dioxide also has a porous structure and can effectively absorb impurities. The two work synergistically to jointly improve the antifouling performance of the adhesive and the viscosity of the tape.
[0088] Further comparison of Example 1 and Comparative Examples 2-3 shows that the present invention adds modified nano titanium dioxide composites to the adhesive, which can not only enhance the adhesive force of the tape, but also enhance the antifouling performance of the tape. Due to its surface modification, the modified nano titanium dioxide composite can provide more active sites, enhance the interaction with the tape substrate, thereby improving the adhesive force, and the modified nano titanium dioxide composite can improve the stability of the tape in a high temperature environment and keep the adhesive performance from decreasing; due to the high surface energy and photocatalytic activity of the modified nano titanium dioxide composite, the super hydrophobic property of perfluoropolyether siloxane can effectively reduce the surface energy of the tape and the interface, thereby improving the hydrophobic property of the adhesive, and ultimately reduce the adsorption of pollutants on the surface of the tape, keeping the tape clean.
Claims
1. A high temperature self-peeling anti-pollution protective tape, characterized in that: It comprises a substrate, a release agent and an anti-pollution protective layer, wherein the anti-pollution protective layer is obtained by uniformly coating a film made of an adhesive on the surface of the substrate; the raw material of the adhesive comprises an anti-pollution additive; and the anti-pollution additive is a modified nano titanium dioxide composite.
2. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The substrate is any one of PE, PP and thermoplastic polyurethane.
3. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The release agent is a silicone release agent.
4. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The adhesive is composed of the following raw materials in parts by weight: 40-70 parts by weight of soft monomer, 5-12 parts by weight of hard monomer, 3-6 parts by weight of functional monomer, 0.5-2 parts by weight of crosslinking agent, 4-7 parts by weight of anti-pollution additive, 0.5-2 parts by weight of di-tert-butyl peroxide, and 150-300 parts by weight of solvent.
5. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The soft monomer is at least one of ethyl acrylate, butyl acrylate, isooctyl acrylate and lauryl methacrylate.
6. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The hard monomer is at least one of methyl acrylate, isopropyl methacrylate, styrene, acrylonitrile, methyl methacrylate and acrylamide.
7. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The functional monomer is one or more of methacrylic acid, 2-hydroxyethyl acrylate, diphenyl (4-vinylphenyl) phosphine oxide, glycidyl acrylate, and N,N-dimethylacrylamide.
8. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The crosslinking agent is at least one of hydroxyethyl acrylate, bis(1-vinyl imidazole-2-)ketone, and 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane.
9. The high temperature self-peeling anti-pollution protective tape according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide composite is as follows: S1. Mix 3-aminopropyl pentamethyldisiloxane, succinic anhydride and N,N-dimethylformamide and stir evenly, add nano-titanium dioxide and perform ultrasound, and then heat and stir to obtain carboxylated titanium dioxide; S2, take methyl 2,6-diisocyanatohexanoate and toluene and stir evenly, then add terminal hydroxyl perfluoropolyether and N-(beta-aminoethyl)-gama-aminopropyltrimethoxysilane, heat and stir, then add γ-glycidyloxypropyltrimethoxysilane, continue to react, and obtain perfluoropolyether siloxane; S3, ultrasonically dispersing the carboxylated titanium dioxide and toluene, adding the perfluoropolyether siloxane, continuing ultrasonication, and finally reacting at 90-100° C. for 4-8 hours to obtain a modified nano-titanium dioxide composite.
10. The method for preparing the high temperature self-peeling anti-pollution protective tape according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: coating a release agent on one surface of a substrate and drying it; then directly coating a film made of an adhesive on the other surface of the substrate, drying it, and rolling it up to obtain a self-peeling anti-pollution protective tape at high temperature.
Citation Information
Patent Citations
Peelable pressure-sensitive adhesive tape without residual adhesive and preparation method of peelable pressure-sensitive adhesive tape
CN118834623A